(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The patriarchal hegemony of translation is denigrated by feminist translation theory. This study aims to both explore the major themes in the literature on feminism and literary translation and to examine the primary methods by which different scholars have used feminist translation theory in their analysis of translated novels. In order to do this, thirty-three research published between 2005 and 2021 have been examined using the databases of EBSCO, ProQuest, Taylor & Francis, ETHOS, and Google Scholar. The research approach employed was a systematic review, and a content analysis method was utilized to analyze the papers. Furthermore, according to other research, feminist translation theory has concentrated on analyzing the transmission of gendered language in the translated text, investigating feminist translation strategies, and analyzing the influence of translator ideology and gender consciousness on the translation process. Researchers studying feminist and translation studies now have a thorough grasp of the state of applied feminist translation theory in the studies that deal with translated novels thanks to the findings.